Effectiveness of Progressive Muscle Relaxation Therapy Against Insomnia Symptoms in Adolescents - Teguh Wahyudi; Mailisna (CV. Get Press Indonesia, 2026)
Insomnia is a common sleep disorder among adolescents and can interfere with their health, emotional well-being, and academic performance. Progressive muscle relaxation is a non-pharmacological technique known to reduce tension and improve sleep. This study aimed to evaluate the effectiveness of progressive muscle relaxation therapy in reducing insomnia symptoms in students at SMP Negeri 31 Padang. Using an experimental pretest–posttest design, the study involved 40 adolescents aged 12–15 years experiencing insomnia, selected through purposive sampling. Participants were divided into experimental and control groups, with the intervention delivered in six sessions over three weeks. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. Paired t-tests were used to analyze changes within the experimental group, and independent t-tests compared outcomes between groups. Univariate findings showed that most participants were 12–13 years old and experienced moderate insomnia. The bivariate analysis indicated a significant decrease in PSQI scores in the experimental group after receiving progressive muscle relaxation therapy (p = 0.000), demonstrating improved sleep quality. Independent t-test results also revealed a significant difference between the experimental and control groups after therapy (p = 0.000), confirming the superior effectiveness of the intervention. These results show that progressive muscle relaxation can serve as an effective non-pharmacological alternative for managing insomnia among adolescents. Implementing this therapy in school settings may help enhance students’ sleep quality and overall mental well-being.